Hypothyroidism following Hemithyroidectomy. (2nd September 2014) - Merchavy, Shlomo; Marom, Tal; Forest, Veronique‐Isabelle; Wolff, Benjamin M.; Mlynarek, Alex M.; Hier, Michael P.; Payne, Richard J.
Abstract : Objectives: Assess the rate of hypothyroidism following hemithyroidectomy. Methods: A retrospective study in adult patients undergoing hemithyroidectomy at the McGill University Thyroid Cancer Centre, during the years 2007 through 2012. Patients with preoperative hypothyroidism were excluded. Patients were followed 12 to 60 months after the primary surgery, and preoperative thyroid stimulating hormone (TSH) and free T4 levels were compared before and after the surgery. Hypothyroidism was defined as TSH levels >4.5 mU/L. Results: Of the 181 eligible patients in this study, 137 (75%) were females, with a mean age of 49.1 ± 14.3 years. The most common indication for surgery was follicular lesion. Hypothyroidism occurred in 65 (35%) of the patients, and was diagnosed at 1 to 36 months after surgery. Age and sex were not found to be risk factors for post‐hemithyroidectomy hypothyroidism. Conclusions: In this study 35% of patients undergoing hemithyroidectomy develop postoperative hypothyroidism. Upon preoperative patient counseling, hypothyroidism is a major morbidity that should be thoroughly discussed.